INTERACTION PATTERN OF NON-MUSLIM STUDENTS OF UNIVERSITAS MALIKUSSALEH - Setiawan, Ade Lucky; Al Usrah, Cut Rizka; Saifuddin, Saifuddin; Rizki, Dini (FISIP Universitas Malikussaleh, 2025)
This study examines the interaction pattern of non-Muslim students at Malikussaleh University. The main focus in this study is how the interaction pattern of non-Muslim students of Malikussaleh University and how the form of tolerance between the community and non-Muslim students of Malikussaleh University is formed. This research uses the theory of symbolic interactionism from George Herbert Mead. This study uses a qualitative research method with a descriptive approach that aims to understand and describe the phenomena experienced by the research subjects. The data collection techniques used were observation, guided free interviews, and documentation. Data analysis is used through the stages of data reduction, data presentation, and conclusion drawn. The results of this study show that the interaction pattern of non-Muslim students at Malikussaleh University is cooperation between non-Muslim students and Muslim students. Meanwhile, the form of tolerance for non-Muslim students is intra-religious tolerance and inter-religious tolerance.